Karyotypes of some species of the genus Lessingianthus (Vernonieae, Asteraceae) and taxonomic implications - Angulo, Maria Betiana (2015)
We determined the karyotypes of nine species of Lessingianthus, eight of which are here analyzed for the first time. The results include the first chromosome count for L. plantaginoides, which is tetraploid with 2n=64. All species showed a high proportion of metacentric chromosomes combined with a lower proportion of submetacentric pairs. Only L. coriaceus had a subtelocentric chromosome pair. B chromosomes were observed in L. coriaceus and L. varroniifolius, which were subtelocentric. Differences among the karyotypes of the studied species were small, suggesting that karyotype diversity in the genus evolved by small changes in the structure of chromosomes. Karyotype features appear useful to distinguish Lessingianthus from the closely related genera Chrysolaena and Lepidaploa.